Development of Nepenthes diversity module at Mount Sibuatan for Biology learning - Arif Fadila; Miza Nina Adlini (Himpunan Pengembang Kurikulum Indonesia, 2025)
The biodiversity of pitcher plants (Nepenthes sp.) on Mount Sibuatan faces serious threats due to pollution and human activities. However, specific teaching materials related to this endemic species are still minimal in high school biology education. This study developed a local-potential-based learning module on Nepenthes diversity on Mount Sibuatan to improve student understanding and conservation awareness. Using the Research and Development method using the ADDIE model, data were collected through field exploration on the Naga Lingga trail, analysis of the Merdeka curriculum, expert validation, and practicality and effectiveness tests at MAN Batubara. The study identified four Nepenthes species: N. tobaica, N. spectabilis, N. rhombicaulis, and one other species. The module obtained very good validity from media and material experts. Implementation showed high effectiveness, with significant improvement from pretest to posttest. This module proved effective in increasing conceptual understanding and creating protection enlightenment, while developing student character based on Pancasila values, critical thinking, and environmental awareness through the integration of local knowledge in biology learning. Abstrak Keanekaragaman hayati tumbuhan kantong semar (Nepenthes sp.) di Gunung Sibuatan menghadapi ancaman serius akibat pencemaran dan kegiatan manusia. tetapi, bahan ajar khusus terkait spesies endemik ini masih minim pada pendidikan hayati Sekolah Menengan Atas. Penelitian ini mengembangkan modul pembelajaran berbasis potensi lokal tentang keragaman Nepenthes di Gunung Sibuatan untuk meningkatkan pemahaman peserta didik dan kesadaran konservasi. menggunakan metode Research and Development menggunakan model ADDIE, data dikumpulkan melalui eksplorasi lapangan di jalur Naga Lingga, analisis kurikulum Merdeka, validasi ahli, serta uji kepraktisan dan efektivitas pada MAN Batubara. Penelitian mengidentifikasi empat spesies Nepenthes: N. tobaica, N. spectabilis, N. rhombicaulis, serta satu spesies lainnya. Modul memperoleh validitas sangat baik dari ahli media dan materi. Implementasi menunjukkan efektivitas tinggi, menggunakan peningkatan signifikan dari pretest ke posttest. Modul ini terbukti efektif dalam menaikkan pemahaman konseptual serta menciptakan pencerahan perlindungan, sekaligus menghasilkan karakter peserta didik berlandaskan nilai-nilai Pancasila, pemikiran kritis, dan kepedulian lingkungan melalui integrasi pengetahuan lokal pada pembelajaran hayati. Kata Kunci: Gunung Sibuatan; kanotng semar; modul pembelajaran; Nepenthes